(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
An active lifestyle and nutritional habits are fundamental components in supporting the performance of Pencak Silat athletes, a highly physically demanding martial art. This study aimed to conduct a literature review of 18 studies published between 2015 and 2024 to map the relationship between nutritional intake, body composition, hydration, physical activity, and other lifestyle factors on athlete performance. The research method used a literature review design with data search through the Scopus, PubMed, Web of Science, Google Scholar, and Garuda databases. The analysis results showed that most athletes still experience energy deficits and imbalances in macronutrient intake, while nutritional knowledge is relatively low. Body composition, especially muscle mass and fat percentage, plays a crucial role in determining strength, speed, and technical skills. Hydration status is also a critical issue, as rapid weight loss practices (weight cutting) cause dehydration and decrease cognitive function and performance. Furthermore, lifestyle factors such as sleep quality, recovery, and unsupervised supplement use also affect training adaptability. This study concluded that a holistic approach is needed in developing Pencak Silat athletes, including nutrition education, hydration management, nutritional periodization, and regular body composition monitoring. Further research using longitudinal and interventional designs is recommended to strengthen the evidence for causality and generate more applicable nutritional guidelines.